Family Education Model Based on Ibadurrahman Values in QS Al-Furqan 63-74 from the Perspective of Tafsir Al-Munir - Fajrin, Fina Aulia; Makhful, Makhful (UIR Press, 2026)
This study aims to analyze the values of Ibadurrahman in QS. Al-Furqan verses 63–74 based on the perspective of Tafsir Al-Munir by Wahbah Az-Zuhaili and examine its relevance to character education in the family. This study uses a library study method by examining primary sources in the form of tafsir books and secondary sources in the form of books, journals, and relevant scientific research. The results of the study indicate that the values of Ibadurrahman include the attitude of tawadhu', politeness in communication, the ability to control emotions, commitment in worship, and a life orientation based on the values of the Qur'an. These values have strong relevance to the process of character development of children in the family environment, especially in forming religious attitudes, self-control, and polite social behavior. Based on the results of the analysis, this study formulates a conceptual model of family education based on the values of Ibadurrahman which includes the objectives of character formation, habituation strategies in the family, and indicators of children's character achievement. This model is expected to be a conceptual framework in strengthening character education based on the values of the Qur'an in the family environment.